Rethinking the Human Condition: Skepticism, Realism, and Transactional Pragmatism. - Ryan, Frank X. (Contemporary Pragmatism, 2016)
For several decades, renewed interest in the connection between perception and knowledge has sustained a robust debate over external world skepticism (EWS). Recently, however, a growing consensus claims the skeptical challenge has been substantially met, and that realism in some robust form has emerged a clear victor. I invite us to rethink this consensus in a two-part response. The first forges a temporary alliance with skepticism against prominent forms of contemporary realism. That these fail to rebuff ews bolsters Barry Stroud's call for a new paradigm of objectivity. In the second part I sketch such a paradigm based upon a transactional interpretation of John Dewey's pragmatism, and indicate its resilience to skeptical attacks.